Jobactive and young job seekers: Strengths, limitations, and suggested improvements to current practices. Issue 4 (17th May 2019) - Moore, Katherine
Abstract: This paper explores the efficacy of current employment services in Australia, jobactive, from the perspectives of young job seekers and their employment officers. As high youth unemployment rates and the efficacy of jobactive employment services are currently areas of priority for the Australian Government, the study offers a timely contribution to the social policy and youth employment literature by exploring the tensions experienced by young job seekers while registered with a jobactive provider, and employment officers when assisting young people to find sustainable employment. The study analyses data from 46 interviews with young job seekers and their employment officers in an outer western Melbourne region. The findings reveal particular concerns about appropriate and adequate service provision for marginalized young job seekers that are similar to those in evaluations of previous marketwise employment service contracts, Job Network and Job Services Australia. Suggestions for tailored employment assistance for young job seekers to gain sustainable employment are offered for future consideration. Abstract : The study offers a timely contribution to the social policy and youth employment literature by exploring the tensions experienced by young job seekers whilst registered with a jobactive provider, and employment officers when assisting young people to find sustainable employment. The findings reveal particular concerns about appropriate and adequate service provision for marginalised young job seekers that are similar to those in evaluations of previous marketised employment service contracts.